Kekerasan Majikan Terhadap Asisten Rumah Tangga (ART): Analisis Sosio-Pastoral atas Relasi Kuasa dan Peran Profetik Gereja - Koli, Endang Damaris (Sekolah Tinggi Teologi Baptis Indonesia, 2025)
This article analyzes the phenomenon of employer violence against domestic workers in Indonesia as a deeply rooted social issue embedded in the structures of household power. Employing a qualitative socio-theological approach, the study examines five documented cases of employer-perpetrated violence against domestic workers from 2022 to 2025, based on reports from nationally recognized media outlets. The analysis is framed by Pierre Bourdieu’s theories of habitus and symbolic violence, alongside Gustavo Gutiérrez and Allan Boesak’s model of pastoral prophetic theology. The findings reveal that such violence is not merely the result of individual moral failure but rather a manifestation of normalized, structured dominance within domestic spaces. From a theological perspective, this violence constitutes a form of structural sin that calls for a prophetic and transformative response from the Church. The article recommends a pastoral repositioning that goes beyond empathy for victims to include critical engagement with the power dynamics that sustain abuse. This includes ethical education within congregations, the development of penitential liturgies for employers, and the Church’s participation in public advocacy for the legal protection of domestic workers. Ultimately, this study contributes to the development of a contextual pastoral theology in Indonesia that prioritizes human dignity and social justice.